Cairo-Berlin Return: Early Arab-German Cooperation in Film – The Egyptian-German Example (Global Media Journal - German Edition, 2021)
The Arab-German cooperation in film began after World War I in 1919/1920 when the first Egyptians came to learn the then brand new art in Germany, and has been continuing with different Arab partners ever since. Yet there is neither a public nor a professional awareness of this history. When Arab and German film professionals meet at international co-production platforms today, they practically get together as strangers. Despite its richness, the common history does not serve as a point of reference. It is not written. This paper, therefore, attempts to shed light on this forgotten period of cooperation. It looks at how and why such a collaboration was initiated. Moreover, it describes its different formats and also why the Egyptian-German encounter eventually came to an end.
Keywords: cinema; pioneers; sound-movies; Weimar Republic; Egypt; anti-colonial liberation; international co-production; transnational cooperation